COVID-19 Post-Pandemic Agricultural Extension Services: A Strategic Analysis of Post-Pandemic Sustainability - Sanjenbam Sher Singh; Rajkumar Josmee Singh; Loukham Devarani; L. Hemochandra; Ram Singh; Anju Choudhury (Archives of Current Research International, 2025)
The COVID-19 pandemic profoundly disrupted agricultural extension systems worldwide, highlighting systemic vulnerabilities while accelerating digital transformation. This paper presents a comprehensive analysis of post-pandemic extension services, emphasizing sustainability, inclusivity, and resilience. It explores the breakdown of traditional service delivery due to lockdowns and movement restrictions and examines the rapid pivot toward digital platforms such as mobile apps, AI tools, and hybrid models that blend in-person and virtual engagement. The study identifies critical challenges, including digital inequality, labor shortages, trust deficits, infrastructural gaps, and market disconnection. Drawing from global case studies—India, Kenya, the Philippines, and the U.S.—the paper highlights best practices like public-private partnerships, community media, and localized content. A sustainability framework is proposed, encompassing farmer-centric approaches, digitally inclusive infrastructure, multi-stakeholder ecosystems, and crisis-ready systems. Policy recommendations focus on capacity development, monitoring and evaluation, and decentralized, culturally relevant service models. The findings underscore the need to reimagine agricultural extension as a dynamic, integrated, and digitally enabled system that centers farmer empowerment, equity, and adaptability in the face of future crises.